Contributions of rural area education to omnilateral formation (Research, Society and Development, 2020)
The present paper addresses the issue of rural area education and comes up with the purpose of thinking about its possible contributions to an omnilateral formation. For this purpose, we used bibliographic research as a methodology. We begin with a brief analysis of the history of rural area education in Brazil, with all the struggles and achievements, we continue to differentiate between rural education and rural area education, since they, although often treated as if they were the same type education, have specific characteristics. Rural education characterized by reproducing urban education in rural areas, rural area education seeks not only to value peasant identity, but to act in favor of the emancipation of rural subjects. The article presents a brief definition of omnilateral training, while a training that encompasses all dimensions of the humanization process of the subjects. It is inferred that rural area education can provide important contributions so that omnilateral formation takes place, following the example of the ethical-political character given to educational activities, the search for overcoming the paradigm of capitalist production and the struggle for the construction of a new model of society based on sustainable development.